2018
DOI: 10.5194/hess-2018-519
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Large-scale ERT surveys for investigating shallow regolith properties and architecture

Abstract: Abstract. Within the Critical Zone, regolith plays a key role in the fundamental hydrological function of water collection, storage, mixing and release. Electrical Resistivity Tomography (ERT) is recognized as a remarkable tool for characterizing the geometry and properties of the regolith, overcoming limitations inherent to conventional borehole-based investigations. However, ERT measurements with a high vertical resolution remain restricted to shallow depths, essentially due to the requirement of small elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 64 publications
1
35
0
Order By: Relevance
“…A more stable percentage of contribution seemed to be associated to the reaches located in the middle and west part of the stream (i.e., reaches M3, M2, M1, and L1), in contrast to the reaches located in the east (R2 and R2) and lower part (S2) of the stream. As previously mentioned, the investigations of Gourdol et al () employing soil drilling and electrical resistivity tomography revealed some heterogeneities in the subsurface structure of the Weierbach catchment. In particular, they have shown that the northern and western part of the catchment is characterized by overall thinner solum (i.e., “true soil,” where pedogenic processes are dominant; cf.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A more stable percentage of contribution seemed to be associated to the reaches located in the middle and west part of the stream (i.e., reaches M3, M2, M1, and L1), in contrast to the reaches located in the east (R2 and R2) and lower part (S2) of the stream. As previously mentioned, the investigations of Gourdol et al () employing soil drilling and electrical resistivity tomography revealed some heterogeneities in the subsurface structure of the Weierbach catchment. In particular, they have shown that the northern and western part of the catchment is characterized by overall thinner solum (i.e., “true soil,” where pedogenic processes are dominant; cf.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, they have shown that the northern and western part of the catchment is characterized by overall thinner solum (i.e., “true soil,” where pedogenic processes are dominant; cf. Gourdol et al, ) and shallower hard bedrock compared with the eastern portion of the catchment. This may determine differences in the way different sides of the catchment deliver water to the stream.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Those algorithms can lead to inverted ERT images whose resolution is superior or equal, respectively with the same or fewer number of measurements, to those using standard survey designs (for example, Wenner-Schlumberger or dipole-dipole (eg. Stummer et al, 2004;Furman et al, 2004Furman et al, , 2007Wilkinson et al, 2006Wilkinson et al, , 2012Loke et al, 2014;Abdullah et al, 2018;Uhleman et al, 2018)). Thus, in the scope of large-scale ERT C1 surveys, such optimized non-conventional electrode arrays could help reducing the operational measurement time without reducing the information content.…”
mentioning
confidence: 99%